The increase of efficiency of treatment pigs at nematodosis - S. T. Karelin; V. I. Zaycev; N. V. Vorobieva (Российский паразитологический журнал)
The results of improvement 7,5 % solutions of levamisol are stated at the main nematodosis of pigs. The drug in a doze of 7,5 mg/kg is effective, but toxic. To decrease its toxicity have added 1 % of crystal succinic acid that has allowed to increase efficiency on 2,8–8,6 % and to reduce toxicity.